ROLE OF THE FORMAL AND INFORMAL SECTOR IN WEST KALIMANTAN - Iva Ashari Ananada (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
The formal sector and the informal sector run with their respective changes, the informal sector becomes a buffer from the structural transformation of unbalanced employment. When it was realized that the informal sector was able to provide significant contributions both in terms of employment and output capacity, the perspective of this sector changed. The informal sector is no longer a crutch but also a complex alternative to the formal sector.